Impact of Janus Kinase Inhibition on the Treatment of Axial Spondyloarthropathies - Hammitzsch, Ariane; Lorenz, Georg; Moog, Philipp (Frontiers in Immunology, 2020)
Many immune cells and effector molecules (e.g. cytokines, Interferons, growth factors) utilize different combinations of Janus Kinase (JAK) and Signal Transducers and Activators of Transcription (STAT) molecules to transduce signals from the cell surface to the nucleus, where they regulate transcription. This pathway is basically involved in almost all inflammatory diseases and also in the Interleukin (IL)-23/IL-17 cascade which has been shown to be an essential part of the pathogenesis of Spondy-loarthropathies (SpA). Upon evidence from in-vitro and in-vivo experiments indicating disease modi-fying effects of JAK inhibition in inflammatory joint disease numerous inhibitors of the JAK/STAT pathway (=JAKinibs) with different selectivity against the four members of the JAK family (JAK1, JAK2, JAK3 and Tyrosine kinase 2 (TYK2)) were developed. Trials in Rheumatoid Arthritis (RA) were successful with respect to efficacy and safety, and currently three JAKinibs are approved for the treatment of RA in the EU. Although new treatment options (anti-IL-23, anti-IL-17, Phosphodiesterase 4 (PDE4) inhibitors) have become available for SpA and especially Psoriatric Arthritis (PsA) within the last years, most of them are biologics and do not address all disease manifestations equally. Therefore multiple trials were initiated to evaluate JAKinibs in PsA and axial SpA (axSpA). A trial of Tofacitinib (OPAL) was successful in PsA and has led to the inclusion of JAKinibs into the treatment algorithm. Currently many trials with JAKininbs are ongoing for PsA and axSpA, with one Phase III trial of upadacitinib (selective JAK1 inhibitor) showing good therapeutic response in active radiographic axSpA.